Sejarah Permulaan Percetakan Al-Quran dan Penggunaan Rasm Uthmani - Khairul Anuar Mohamad; Mohd Zaini Zakaria; Anuar Hasin (Universiti Sains Islam Malaysia, 2024)
PAPER PROCEEDINGS THE 7TH INTERNATIONAL CONFERENCE ON QURAN AS FOUNDATION OF CIVILIZATION (SWAT) 2021 “ISLAMIC AND NON-REVEALED KNOWLEDGE IN FACING THE GLOBAL CHALLENGES” 6th – 7th October 2021 / 29 – 30 Safar 1443H Faculty of Quranic and Sunnah Studies Universiti Sains Islam Malaysia